Studi Kontribusi Perceived Organizational Support terhadap Stres Kerja pada Bank X Cabang Utama Bandung - Ghifany Ramadhanty; Ali Mubarak (Bandung Conference Series: Psychology Science, 2023)
Abstract. Perceived Organizational Support is the general beliefs and beliefs of employees about the extent to which the organization values ​​their contributions and cares about the welfare of employees (Eisenberger et al., 1986). When employees have positive perceived organizational support, they will produce positive outcomes. Based on previous research, perceived organizational support has a negative relationship with work stress. According to Parker & DeCotiis (1983) job stress is an event that occurs in the work environment with feelings that deviate from normal as a result of the conditions they feel. This study aims to see the magnitude of the contribution of perceived organizational support to work stress. This research is a quantitative research with a correlational approach that is causal in nature. Using non-probability sampling technique with accidental sampling technique [convenience sampling]. Respondents of this study consisted of 149 employees of Bank X Cabang Utama Bandung. Using the Perceived Organizational Support measurement tool which has been adapted by Rahmi, T., Agustiani, H., Harding, D., & Fitriana, E. [2021] and Work Stress which has been adapted by Resi & Anggriani [2021]. The results of this study indicate that Perceived Organizational Support contributes significantly to Job Stress by 60.5%. Abstrak. Perceived Organizational Support adalah keyakinan umum dan kepercayaan karyawan tentang sejauh mana organisasi menghargai kontribusi mereka dan peduli tentang kesejahteraan karyawan (Eisenberger et al.,1986). Ketika karyawan memiliki perceived organizational support yang positif, akan menghasilkan outcome yang positif. Berdasarkan penelitian sebelumnya perceived organizational support ini memiliki hubungan yang negative dengan stres kerja. Menurut Parker & DeCotiis [1983] stres kerja adalah kejadian yang terjadi dalam lingkungan kerja dengan perasaan yang menyimpang dari normalnya sebagai akibat dari kondisi yang dirasakannya. Penelitian ini bertujuan untuk melihat besarnya kontribusi perceived organizational support terhadap stres kerja. Penelitian ini merupakan penelitian kuantitatif dengan jenis pendekatan korelasional yang bersifat kausalitas. Menggunakan teknik sampling non probability sampling dengan teknik accindental sampling [convenience sampling]. Responden penelitian ini terdiri dari 149 pada Karyawan Bank X Cabang Utama Bandung. Menggunakan alat ukur Perceived Organizational Support yang telah diadaptasi Rahmi, T., Agustiani, H., Harding, D., & Fitriana, E. [2021] serta Stres Kerja yang telah diadaptasi oleh Resi&Anggriani [2021]. Hasil penelitian ini menunjukkan bahwa Perceived Organizational Support berkontribusi secara signifikan terhadap terhadap Stres Kerja sebesar 60,5%.